Human Liver Stem Cell‐Derived Microvesicles Inhibit Hepatoma Growth in SCID Mice by Delivering Antitumor MicroRNAs123. (20th August 2012) - Fonsato, Valentina; Collino, Federica; Herrera, Maria Beatriz; Cavallari, Claudia; Deregibus, Maria Chiara; Cisterna, Barbara; Bruno, Stefania; Romagnoli, Renato; Salizzoni, Mauro; Tetta, Ciro; Camussi, Giovanni
Abstract: Microvesicles (MVs) play a pivotal role in cell‐to‐cell communication. Recent studies demonstrated that MVs may transfer genetic information between cells. Here, we show that MVs derived from human adult liver stem cells (HLSC) may reprogram in vitro HepG2 hepatoma and primary hepatocellular carcinoma cells by inhibiting their growth and survival. In vivo intratumor administration of MVs induced regression of ectopic tumors developed in SCID mice. We suggest that the mechanism of action is related to the delivery of microRNAs (miRNAs) from HLSC‐derived MVs (MV‐HLSC) to tumor cells on the basis of the following evidence: (a) the rapid, CD29‐mediated internalization of MV‐HLSC in HepG2 and the inhibition of tumor cell growth after MV uptake; (b) the transfer by MV‐HLSC of miRNAs with potential antitumor activity that was downregulated in HepG2 cells with respect to normal hepatocytes; (c) the abrogation of the MV‐HLSC antitumor effect after MV pretreatment with RNase or generation of MVs depleted of miRNAs; (d) the relevance of selected miRNAs was proven by transfecting HepG2 with miRNA mimics. The antitumor effect of MV‐HLSC was also observed in tumors other than liver such as lymphoblastoma and glioblastoma. These results suggest that the delivery of selected miRNAs by MVs derived from stem cells may inhibit tumor growth and stimulate apoptosis. Stem Cells 2012;30:1985–1998